Caracterização de frutos, divergência genética e estrutura espacial de jaboticabeiras nativas de fragmento florestal em Clevelândia - PR - Paladini, Marcos Vily (2016)
To design strategies for the conservation and use of genetic resources of tree species such as jaboticaba tree, it is essential to make the characterization. In southwestern Paraná region, there are several forest fragments containing native jaboticaba tree (Plinia cauliflora), whose materials have broad potential for commercial orchards or breeding programs. As is the potential genetic diversity of a population to produce different genotypes, it would be able to start in such a characterization one of these fragments. The aim was to characterize fruits of jaboticaba tree (P. caulifora) of forest fragment kept in Clevelândia - PR for the presence of phenotypic variability, seeking to identify those superiors named for future selection as farming or male parent, as well as estimate genetic divergence between them, as a complementary tool for this purpose. Also, verify the regeneration and spatial distribution of the species. For the study was defined portion of a hectare (10.000 m²), with all individuals identified, mapped, with local coordinate system, and measured height and diameter. Fruits were characterized by sensory and biochemical characteristics in two years, 70 genotypes at 2013 and 56 at 2014, and of these 33 genotypes in both years. As a pre-selection criteria was adopted the choice of 20% of the genotypes that showed the highest frequency of superiority in the evaluated characteristics of the fruit. Genetic divergence among 33 genotypes per year was analyzed. The distribution pattern and spatial association was evaluated by Ripley's K function. It was classified for the first time the following ontogenetic stages of jaboticaba tree, by plant height, seedling (from 0.01 to 0.99 m), juvenile (1.0 to 4.99 m), immature (> 5.0 m, non-reproductive), adult (reproductive). It was also have been describe for the first time the naturally occurring juxtaposed seedlings, indicating polyembryony. The number of regenerating identified in the population (seedlings: n = 2163; juveniles: n = 330; immature: n = 59) was much larger than the number of adults (n = 132). The species showed reverse J-shaped size structure standard, with high concentration of regenerating. The regeneration distribution occurs in aggregate pattern and there is seedling-adult dependence, due seed dispersal and seedling emergence closest to mothers. The jaboticaba tree regeneration is sufficient to maintain the species for long term in this population, which should serve as reference to regeneration success for other studies of this important fruiting species from Ombrofile Mixed Forests. Has been pre-selected the jaboticaba trees 7, 42, 43, 47, 54, 91, 97, 104, 105, 118, 134, 153, 154, 157, 163, 169, 177, 186, 212, J7-01 and J7- 02, and 16 and 194 the ones that can now be selected by the superior characteristics of both cycles. It was recommended to carry out hybridization between genotypes 79 and 119, and 96 to 148. The quality of fruit analyzed showed potential for use as a dual purpose serving both in natura market or processing.